SISTEM REKRUTMEN DAN PENGKADERAN ANGGOTA PARTAI GOLONGAN KARYA KABUPATEN MUSI BANYUASIN PADA TAHUN 2009 – 2014 - Adi Widagdo Wicaksono; Amaliatulwalidain Amaliatulwalidain (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
Golkar is a democratic party that is committed to democracy . A party which is actually a major party has a solid infrastructure, entrenched, loyalty , and responsive , already quite experienced in Indonesia in recruiting cadres - cadres to be positioned in the organizational structure and placed in the government , and has a track record of its own citizens to assess how football the party exploits over the years. Recruitment and regeneration by political parties is a continuation of the function seize , retain and use power . The results obtained from this study were (1) Class work in recruiting new members do not have runway specific rules and conditions. Specific requirements that must be owned by a person to become a member of the party was not there. All requirements specified in the work group are general and not difficult for citizens to join the party. (2) in the recruitment and cadre, Golkar recruited all segments of society. In the face of the Golkar had training in the training of cadres in which party members will be given the political education that will better political knowledge. (3) recruitment and cadre are used Golkar is a system Stelsel active, ie a system that implements that every person who wants to become the party cadres to be active, the implementation of regeneration system Golkar is through four processes, namely: Withdrawal (Recruitment), Selection process , Political Education, and Development.Keywords : Recruitment, Cadre, Golongan Karya